2019
DOI: 10.1016/j.stemcr.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Nuclear Receptor TLX Represses Hes1 Expression, Thereby Affecting NOTCH Signaling and Lineage Progression in the Adult SEZ

Abstract: Summary In the adult subependymal zone (SEZ), neural stem cells (NSCs) apically contacting the lateral ventricle on activation generate progenitors proliferating at the niche basal side. We here show that Tailless (TLX) coordinates NSC activation and basal progenitor proliferation by repressing the NOTCH effector Hes1 . Consistent with this, besides quiescence Hes1 expression also increases on Tlx mutation. Since HES1 levels are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…To determine in what subclusters Lrig1 expression is the highest, we calculated the mean expression level within each subcluster. To verify the accuracy of the result, several well-known marker genes were also analyzed: Nr2e1 [40,41], Ascl1 [42], and Dcx. As expected, this analysis revealed that Nr2e1 and Ascl1 expression levels peaked in activated stem cells, and Dcx expression level peaked in neuroblasts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine in what subclusters Lrig1 expression is the highest, we calculated the mean expression level within each subcluster. To verify the accuracy of the result, several well-known marker genes were also analyzed: Nr2e1 [40,41], Ascl1 [42], and Dcx. As expected, this analysis revealed that Nr2e1 and Ascl1 expression levels peaked in activated stem cells, and Dcx expression level peaked in neuroblasts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in proliferation pattern between the two genotypes may reflect the greater role that Tlx plays in activated apical NSCs and TAPs, where the orphan nuclear receptor was found to be particularly highly expressed. Likewise, activated apical NSCs and TAPs, which are absent in Tlx -/mice, may be necessary to transmit Notch signaling across the apical/basal axis of the niche and this can be the explanation of the different results obtained from WT and Tlx -/mouse model studied before (Luque-Molina et al 2019) . However, we cannot exclude the possibility that Hes1 expression, which in the absence of Tlx is also increased in basal progenitors, prevents the downregulation of Notch activation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Wildtype and hGFAP-tTA;H2B-GFP (hGFAP;H2B-GFP) mice were sacrificed by CO2 inhalation followed by cervical dislocation (adult), or by decapitation (neonatal). For DiI analyses, brains were placed on a petri dish, the V-SVZ apical surface was exposed and DiI (1,1'-Dioctadecyl-3,3,3',3'-Tetramethylindocarbocyanine Perchlorate, ThermoFisher Scientific) was applied for 1 minute followed by washing in sort medium (Luque-Molina et al 2019). The V-SVZ was dissected and clonal analysis was performed as previously described (Ciccolini et al 2005).…”
Section: Animals and Svz Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the C. elegans tll orthologue nhr-67 regulates both lin-12 (Notch) and lag-2 (Delta) during uterus development (Verghese et al, 2011). Strikingly, in the mouse brain, the tll orthologue Nr2E1 (aka Tlx ) was recently shown to negatively regulate the canonical Notch target gene Hes1 (Luque-Molina et al, 2019). Against this backdrop, it is tempting to speculate that the group NB delamination normally observed in the procephalic region results, at least in part from tll repression of the Notch pathway.…”
Section: Discussionmentioning
confidence: 99%